Potensi Daya Tarik Wisata Tari Barong Di Bali - Tria Yuliana; Vanya Alma Earlyana; Alvia Rizqia (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Barong dance is one of Indonesia's cultural treasures that has great tourist attraction potential in Bali. This dance depicts the fight between good and evil in Balinese culture and has the beauty of dance movements, interesting costumes, and stories raised in the dance. Barong dance also has an important role in introducing Balinese culture to tourists and having a positive impact on the local economy. However, in an effort to preserve it, there are several challenges that must be faced, such as maintaining authenticity, quality of appearance, effective promotion, and management and maintenance of costumes and property. Therefore, joint efforts from the government, community, and tourism industry players are needed to maintain and preserve Barong dance properly. In addition, education and training for the younger generation also need to be improved to help maintain the sustainability of Barong dance as a valuable cultural heritage. By maintaining and preserving Barong dance, it is hoped that Balinese culture can continue to be known and appreciated by tourists, and have a positive impact on the local economy.